Answer:
Solve the system of equations.
−
5
x
+
4
y
=
3
x
=
2
y
−
15
−5x+4y=3
x=2y−15
Explanation:
We are given that
x
=
2
y
−
15
x=2y−15start color #6495ed, x, end color #6495ed, equals, start color #6495ed, 2, y, minus, 15, end color #6495ed. Let's substitute this expression into the first equation and solve for
y
yy as follows:
−
5
x
+
4
y
=
3
−
5
⋅
(
2
y
−
15
)
+
4
y
=
3
−
10
y
+
75
+
4
y
=
3
−
6
y
=
−
72
y
=
12
−5x+4y
−5⋅(2y−15)+4y
−10y+75+4y
−6y
y
=3
=3
=3
=−72
=12
Hint #22 / 3
Since we now know that
y
=
12
y=12start color #ff00af, y, end color #ff00af, equals, start color #ff00af, 12, end color #ff00af, we can substitute this value in the second equation to solve for
x
xx as follows:
x
=
2
⋅
y
−
15
x
=
2
⋅
12
−
15
x
=
9
x
x
x
=2⋅y−15
=2⋅12−15
=9
Hint #33 / 3
This is the solution of the system:
x
=
9
y
=
12
x=9
y=12
X= 9
y= 12